Pengembangan e-Thno Comic pada Materi SPLTV untuk Meningkatkan Literasi Matematika Peserta Didik - Siti Nurhaliza; Nonik Indrawatiningsih (PendIPA Journal of Science Education, 2026)
Students’ mathematical literacy in Indonesia is considered relatively low, partly due to the limited availability of supporting learning materials. Therefore, the development of innovative instructional materials is needed to enhance mathematical literacy. An ethnomathematics approach has the potential to improve students’ understanding and learning motivation while supporting contextual learning and strengthening character education. This approach emphasizes key aspects of mathematical literacy, including the ability to formulate, apply, interpret, and evaluate mathematical concepts within cultural and real-life contexts. This study aims to develop an e-thno comic on the topic of systems of linear equations in three variables that meets the criteria of validity, practicality, and effectiveness in improving students’ mathematical literacy. The development model used in this research is ADDIE. The e-thno comic was tested on 20 vocational high school students. Data were collected through validation sheets, mathematical literacy pre-tests and post-tests, and student response questionnaires. The data were then analyzed to determine the validity, practicality, and effectiveness of the developed media. The results show that the e-thno comic is categorized as highly valid, with a validity score of 86.11%. It is also considered highly practical, based on student response questionnaire results with a score of 89.41%. Furthermore, the e-thno comic is proven effective, as indicated by an N-Gain score of 0.61 and a 61% increase in the average pre-test and post-test scores. Therefore, the developed e-thno comic meets the criteria of validity, practicality, and effectiveness and can be used as an alternative learning medium to enhance students’ mathematical literacy.